2024
DOI: 10.1002/ncp.11137
|View full text |Cite
|
Sign up to set email alerts
|

Completion of a Nutrition‐Focused Physical Exam with hospitalized adults and pediatric patients: Secondary analysis of a prospective cohort study

Elizabeth Yakes Jimenez,
Erin Lamers‐Johnson,
Julie M. Long
et al.

Abstract: BackgroundNutrition‐Focused Physical Exam (NFPE) feasibility is not well‐studied. We describe registered dietitian nutritionist (RDN)–reported NFPE completion for hospitalized adult and pediatric patients overall and by assessment parameters.MethodsTrained RDNs systematically conducted NFPEs for hospitalized adult and pediatric patients during the Academy of Nutrition and Dietetics and American Society for Parenteral and Enteral Nutrition Indicators to diagnose Malnutrition multisite cohort study (ClinicalTria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, its operation is relatively complex. A prospective cohort study ( 30 ) revealed that children who had lower nutritional complexity were more likely to complete the NFPE examination compared to those with higher nutritional risk. Moreover, older children were also more likely to complete the examination.…”
Section: Nutritional Status and Evaluation Of Ecmo Childrenmentioning
confidence: 99%
“…However, its operation is relatively complex. A prospective cohort study ( 30 ) revealed that children who had lower nutritional complexity were more likely to complete the NFPE examination compared to those with higher nutritional risk. Moreover, older children were also more likely to complete the examination.…”
Section: Nutritional Status and Evaluation Of Ecmo Childrenmentioning
confidence: 99%